'Tis pity she's a whore : a critical guide - Hopkins, Lisa, 1962- (Continuum Renaissance drama., 2010)
John Ford's tragedy 'Tis Pity She's A Whore was first performed between 1629 and 1633 and since then its themes of incest, love versus duty and forbidden passion have made it a widely studied and performed, if controversial, play. This guide offers students an introduction to its critical and performance history, including TV and film adaptations. It includes a keynote chapter outlining major areas of current research on the play and four new critical essays. Finally, a guide to critical, web-based and production-related resources and an annotated bibliography provide a basis for further indiv.